A Plasma Exosomal Metabolic Profiling of Nonalcoholic Fatty Liver Disease Patients Complicated with Impaired Fasting Glucose - Jiang, Weiyun; Jin, Qiaofei; Li, Chunqing; Xun, Yunhao (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Nonalcoholic fatty liver disease is considered as the hepatic manifestation of metabolic syndrome. Detection of circulating exosomes together with metabolomic analysis of their cargo would provide early signals for metabolic derangements and complications associated with nonalcoholic fatty liver disease. Therefore, this study profiled exosomal metabolome of patients with nonalcoholic fatty liver disease and impaired fasting glucose. Materials and Methods: Plasma exosomes were extracted from nonalcoholic fatty liver disease patients with or without impaired fasting glucose through differential ultracentrifugation. Their metabolite profiles were examined by ultrahigh-performance liquid chrom atography–quadrupole time-of-flight mass spectrometry. Pathway analysis was carried out on platform MetaboAnalyst 4.0. Results: Thirty-nine patients were enrolled, including nonalcoholic fatty liver disease-alone group (n = 26) and age-and gender-comparable nonalcoholic fatty liver disease plus impaired fasting glucose group (n = 13). Although less than and different from their plasma counterparts, a total of 10 significantly differential exosomal metabolites were identified. Nonalcoholic fatty liver disease plus impaired fasting glucose group had higher concentrations of linoleic acid, palmitamide, stearamide, and oleamide, as well as a lower concentration of phosphatidylethanolamine [20:5(5Z,8Z,11Z,14Z,17Z)/20:5(5Z,8Z,11Z,14Z,17Z)]. Pathway analysis showed an obviously changed metabolism of linoleic acid. Conclusion: Metabolomic analysis of plasma exosomes revealed a distinct change in fatty acids and related pathways in nonalcoholic fatty liver disease patients with impaired fasting glucose. These preliminary results provide a metabolomic snapshot and basis for further investigation of exosome biology for these patients Cite this article as: Jiang W, Jin Q, Li C, Xun Y. A plasma exosomal metabolic profiling of nonalcoholic fatty liver disease patients complicated with impaired fasting glucose. Turk J Gastroenterol. 2024;35(2):125-135.